Dr. Maniac vs. Robby Schwartz - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2008)
Robby Schwartz, who likes creating comic strips on his computer, develops a supervillain called Dr. Maniac. Meanwhile, a group of seven kids get trapped in a theme park and Robby comes face to face with his creation.